Implementing “Link Nurses” as Spiritual Care Support in a General Hospital - Cusveller, B. S. (Religions, 2020)
Background: spiritual care by nurses may be omitted from clinical practice when not structurally embedded in daily professional care routines. Method: a mixed method study was designed to measure qualitative and quantitative outcomes of a “link nurse” as a spiritual care resource (LNSC). Data were gathered from nurses (n = 123-86), link nurses (n = 15-18) and patients (n = 131-122) before and after an implementation and education project among (link) nurses. Results: findings show a self-reported increase of competency in providing spiritual care, especially assessment, counseling and referral in nurses, and referral in link nurses. In interviews afterwards, link nurses (n = 10) and nurses (n = 8) indicated more confidence in providing spiritual care. Patients reported high satisfaction with spiritual care by nurses, although differences in satisfaction between measurements before and after the project could not be demonstrated. Referral frequency to chaplaincy increased during the project. Conclusion(s): nurses may be willing to include spiritual care and collaboration as part of their professional role when support is provided by the hospital leadership. Education and practice development in spiritual care are supported by the implementation of link nurses, while the hospital’s leadership needs to take its responsibility to provide preconditions. Intervention evaluation suggested that the wider context of professional practice, collaboration, and organization needs to be addressed as well.